2001
DOI: 10.1002/etc.5620201125
|View full text |Cite
|
Sign up to set email alerts
|

Use of molecular markers to study the effects of environmental impacts on genetic diversity in brown bullhead (Ameirus nebulosus) populations

Abstract: Conservation biology needs sound biological information in order to maintain biological diversity in the face of the current rate of loss. An important component of the information needed is the level of genetic diversity within and between populations, especially for those species faced with exposure to environmental stressors. We applied multilocus DNA profile analysis (highly variable number tandem repeats [HVNTR] and randomly amplified polymorphic DNA [RAPD] techniques) and allozyme analysis to test whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…To avoid these complications, we used a measure of genetic distance that only uses bands themselves (Nei & Li 1979), without invoking Hardy-Weinberg equilibrium. Within each location, tests of population subdivision and comparisons of withinpopulation similarity were based on the similarity coefficient (Leonard et al 1999) for each possible pair of individuals, both within and between populations (Silbiger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid these complications, we used a measure of genetic distance that only uses bands themselves (Nei & Li 1979), without invoking Hardy-Weinberg equilibrium. Within each location, tests of population subdivision and comparisons of withinpopulation similarity were based on the similarity coefficient (Leonard et al 1999) for each possible pair of individuals, both within and between populations (Silbiger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the populations show evidence of being genetically distinct, we tested population subdivision with 1000 random permutations resulting in a test P value based on the ranking of the observed test statistic (relationship of within subpopulation similarity to overall similarity across subpopulations) relative to the set of relationships generated from the permuted data (Leonard et al 1999;Silbiger et al 2001). We report within population measures as similarity and between population measures as distance (1 -similarity).…”
Section: Discussionmentioning
confidence: 99%
“…Exploiting the natural dendritic structure of tributaries within a single catchment demonstrated that genetic diversity and species diversity are lower in isolated environments surrounded by disturbed land. The precise environmental driver that gives rise to this pattern is unknown but previous studies have shown that human alteration of catchment land use can adversely affect water quality and degrade stream channels (Diana, Allan, & Infante, 2006); in turn, flow modifications and poor habitat can also lead to significant losses in diversity and reduced abundance of stream fish (Roy et al, 2005;Silbiger et al, 2001). Overall, parallel effects of land use intensification, largely through conversion of land which was previously dominated by woodland or grassland, resulted in a negative influence on species and genetic diversity of fish across the study area, indicating a significant detrimental effect of disturbed land use on local riverine habitat.…”
Section: Environmental Predictors Of Species and Genetic Diversitymentioning
confidence: 99%
“…This is of concern because it is widely contended that there is a direct relationship between the genetic variability of a population and its ability to adapt to environmental stresses. In this context, the application of parameters of population genetic diversity as monitoring tools of wildlife vulnerability to environmental stress has been increasingly encouraged (Krane et al 1999, Bickham et al 2000, Silbiger et al 2001, Theodorakis et al 2001.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%